Growth Abnormalities in Children with Type 1 Diabetes, Juvenile Chronic Arthritis, and Asthma - Cosimo Giannini; Angelika Mohn; Francesco Chiarelli (International Journal of Endocrinology)
Children and adolescents with chronic diseases are commonly affected by a variable degree of growth failure, leading to an impaired final height. Of note, the peculiar onset during childhood and adolescence of some chronic diseases, such as type 1 diabetes, juvenile idiopathic arthritis, and asthma, underlines the relevant role of healthcare planners and providers in detecting and preventing growth abnormalities in these high risk populations. In this review article, the most relevant common and disease-specific mechanisms by which these major chronic diseases affect growth in youth are analyzed. In addition, the available and potential targeting strategies to restore the physiological, hormonal, and inflammatory pattern are described.